A influência do ritmo circadiano e da sazonalidade na ictiofauna da zona de arrebentação de uma ilha tropical em Ubatuba, SP - Neto, Pedro Dias Barreto (Universidade Federal de São Carlos, 2016)
The surf-zone of sandy beaches acts as nurseries, housing a great number of larval and juvenile fish. Among the available factors in this environment are the possibility of shelter against predators and a rich source of zooplankton. The surf-zone ichthyofauna is often characterized by its low richness and high dominance by one or few species when compared to deeper regions of the ocean, in addition to presenting a low number of resident species. Abundance and composition of the fish community of the surf-zone are subject to abiotic factors (e.g., tidal, wind direction and speed, salinity) as well as seasonal and diel variations. Although the great importance of the surf-zone of sandy beaches for the life cycle of fishes, studies focusing on this environment in Brazilian islands are still scarce. Thus, this project initiated in November 2014 aiming at an ecological study of the ichthyofauna of the surf-zone of Prumirim Island, Ubatuba, SP, analyzing the composition and structure of the fish assemblage taking into account both seasonal and diel variations. Samplings occurred monthly with a beach seine, in the morning and at night at two sites along the beach. We collected a total of 4312 g and 3444 individuals belonging to 21 families and 37 species. The ichthyofauna was characterized by eight annual resident species that use the area in their early life stages as well as the constant occurrence of rare species. Shannon index was the only variable for which variation along the year was explained by the interaction between seasonal and diel factors, with mornings of spring and nights of winter presenting a lower value than remaining periods and seasons. In relation to variation of abundance along the year, seasonality was the most influent factor, with winter presenting the lower value. In an additive way and four times less influent, the diel factor contributed less to explain the variation in abundance along the year along with seasonality, with diurnal periods presenting the highest amount of sampled specimens. The number of species varied in a short scale, i.e., between days and nights, with richness being higher at night. Although the MDS ordination had shown an inconspicuous community structure and composition, it was possible to observe subtle diel and more evident seasonal variations, reflecting in changes in resident species abundance along the spring, summer, autumn and at winter nights.
The influence of diel rhythm and seasonality on the surfzone ichthyofauna of a tropical island in Ubatuba, SP
Keywords: fauna insular; picaré; juvenis; praia arenosa; insular fauna; juveniles; beach seine; sandy beach; CIENCIAS BIOLOGICAS::ECOLOGIA